Material Entanglement and Technology Fetishism in Academic Libraries - Levesque, Lisa (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2020)
This article explores technology fetishism in academic libraries as an irrational form of worship. Academic libraries participate in networks of prestige through their investments in technology and its fetishistic rhetoric. To counter the myth of technology as a neutral good, this article draws on contemporary fetishism theory and specifically the work of Bruno Latour to trace how technology is entangled with social relations and upholds hegemonic power. All technology is laden with human thought, feeling, and intent. However, Modern fetishes are dispersed into culture and obscure these entanglements, hiding materiality and obscuring the visibility of labour. This article considers library technology through the lens of fetishism, specifically considering the ways in which discovery layers shape research. Confronting fetishism enables academic library workers to reimagine more human-centered approaches to technology and to bring to light embedded whiteness and sexism in library practices. There is an urgent need to reconfigure our relationships with technology given its entanglement with research and the unexamined power that fetishism holds.